Reframing Educational Excellence Through Improvement: Change and Continuity in Media Representations - Windle, Joel (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
This article investigates the extent to which media reporting challenges or reinforces socially exclusive models of educational excellence. Media reporting is particularly important in contexts of marketization, as schools compete for students and seek to carve out market niches. Based on an analysis of articles published over five years in a major daily newspaper in the Australian state of Victoria, a highly marketized setting, the findings indicate that reporting ignored social factors contributing to school-level performance. Further, reporting offered a prominent place to socially exclusive schools despite deliberate efforts to diversify the types of school profiled. The analysis points to media appropriation of a science-oriented discourse alongside selective use of data to fit a narrative of principal-led school transformation. The findings have implications for responsible and balanced use of school improvement measures locally and in other education systems.